Conflict Management Solutions for Nahdlatul Ulama Members:Systematic Literature Review Based Study - Saefrudin Saefrudin (Maneggio, 2026)
This study aims to analyze relevant and effective conflict management solutions for members of Nahdlatul Ulama (NU), the largest Islamic organization in Indonesia, founded in 1926. Internal conflict within religious organizations, including NU, is a complex phenomenon influenced by ideological differences, political interests, resource struggles, and leadership dynamics at various structural levels. Through a systematic literature review (SLR) of 40 relevant scholarly sources published between 2021 and 2026, this study identifies, classifies, and synthesizes the most appropriate conflict management strategies for the context of a mainstream Islamic religious organization such as NU. The study results indicate that the most effective conflict management approach for NU members is an integrative model that combines the principles of Islamic moderation (tawassuth, tawazun, i'tidal, and tasamuh) with contemporary conflict management theories such as interest-based negotiation, transformative mediation, and strategic leadership in crisis. NU values ​​have been shown to serve as a normative foundation that strengthens internal cohesion and reduces conflict escalation. This study recommends the development of NU value-based conflict management training modules at all levels of the organization and the strengthening of the role of kyai and ulama figures as effective cultural mediators.